Achieving a Near-Infrared Absorption by A−DA’D−A Type Isoindigo-Based Small Molecular Acceptors for Organic Photovoltaics - Hui Liu; Yu Wu; Dong-Nai Ye; Na Chen; Xu-Min Huang; Shi-Yong Liu (Molecules)
Isoindigo (IID)-based non-fullerene acceptors, known for their broad absorption spectra and high charge carrier mobilities, play a crucial role in organic photovoltaics. In this study, two A−DA’D−A type unfused ring acceptors (URAs), IDC8CP-IC and IDC6CP-IC, were designed and synthesized using cyclopentadithiophene (CPDT) and IID core units, each functionalized with different alkyl chains (2-hexyldecyl and 2-octyldodecyl), through an atom- and step-efficient direct C–H arylation (DACH) method. Both URAs, despite the absence of non-covalent conformation locking between CPDT and IID, demonstrated favorable molecular planarity, broad absorption ranges, low band gaps, and high molar absorption coefficients. Notably, IDC6CP-IC exhibited stronger intermolecular charge transfer and J-aggregation. An organic solar cell (OSC) device based on IDC6CP-IC achieved a power conversion efficiency (PCE) of 3.10%, with a broad photoresponse range extending from 400 to 900 nm. This study highlights the significant impact of alkyl chain engineering on material synthesis, photoelectric properties, and corresponding device performance. Furthermore, DACH is shown to be a promising approach for synthesizing IID-based URAs with near-infrared (NIR) absorption, making it an excellent candidate for bulk heterojunction (BHJ) OSC applications.